Criteria for Risk Stratification of Vulvar and Vaginal Smooth Muscle Tumors: An Evaluation of 71 Cases Comparing Proposed Classification Systems. (January 2018) - Sayeed, Sadia; Xing, Deyin; Jenkins, Sarah M.; Weisman, Paul S.; Buehler, Darya; Warmke, Laura; Uram-Tuculescu, Cora; Bakkum-Gamez, Jamie N.; Howitt, Brooke E.; Cortese, Cherise; Park, Kay J.; Schoolmeester, J. Kenneth
Abstract : Accurate risk stratification of smooth muscle tumors (SMTs) is essential for appropriate patient management. Yet, the rarity of SMTs of the vagina and vulva makes development of a prognostically meaningful classification system challenging. While 2 classification methods for vulvar SMTs and 1 for vaginal SMTs have been proposed, it is our experience that many pathologists tend to apply criteria for uterine SMTs when evaluating vulvovaginal tumors. We retrospectively reviewed a large cohort of vulvovaginal SMTs with clinical follow-up and evaluated which method most accurately classified tumors according to patient outcome. A total of 71 tumors, 53 vaginal (75%) and 18 vulvar (25%), from 71 patients were identified. All tumors were centrally examined for degree of cytologic atypia, morphology (spindled, epithelioid, myxoid), mitotic index per 10 high power fields, atypical mitotic figures, tumor cell necrosis, ischemic necrosis, tumor interface (circumscribed or infiltrative) and margin status. Clinical features were recorded for each patient. Follow-up was available for 63 patients (89%), and ranged from 1 to 234 months (median: 64 mo). While site-specific and uterine criteria showed equally excellent sensitivity in classifying smooth muscle neoplasms as leiomyosarcoma according to patient outcome, uterine criteria showed improved specificity relatively to site-specific methods in classifying tumors as nonsarcoma according to patient outcome. We recommend that uterine SMT criteria and nomenclature be adopted for evaluation and classification of vulvovaginal SMTs. Abstract : Supplemental Digital Content is available in the text.